A report on an unusual presentation of autonomic dysreflexia - Suhaida, S.S.; Julia, P.E. (Malaysian Medical Association, 2012)
A 48-year-old male with complete tetraplegia C6 presented with sweating and flushing of the right half of the face and neck that recurred when lying in supine and left lateral positions. The symptoms subsided immediately upon sitting upright or lying in a right lateral position. The symptoms were associated with occasional mild head discomfort rather than headache and were accompanied by marked elevation of blood pressure, which was 190-200/120-130 mmHg compared to his previous baseline blood pressure of 80-90/50-70 mmHg, and he had a heart rate of 60-70 beats per minute. We believe that post-traumatic syringomyelia, found upon further investigation, was the cause of the Autonomic dysreflexia (AD) in this patient. He was advised to avoid the positions causing the symptoms and the progression of symptoms was monitored regularly. AD might not have been diagnosed in this patient because of the atypical and unusual presentations. Therefore, knowledge and a heightened level of awareness of this possible complication are important when treating individuals with spinal cord injury (SCI).